ASSESSMENT OF JAPANESE ENCEPHALITIS VACCINATION STATUS IN TRIBAL AREAS OF THE MAYURBHANJ DISTRICT OF ODISHA – A COMMUNITY-BASED CROSS-SECTIONAL STUDY - DEBASISH SETHY; MUKTIKANTA SINGH; SHUSHRUTA MOHANTY; LOMAPADA NAYAK; DURGA MADHAB SATAPATHY; SANJAYA KUMAR SAHOO (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Japanese encephalitis (JE) is a vector-borne viral disease that primarily infects swines, equids, and humans. Outbreaks of JE-acute encephalitis syndrome were reported from September to November 2012 and 9th September to 2nd December 2016 in Malkangiri district, Odisha. Due to the paucity of studies on JE transmission, causation, and prevention in tribal areas, the present study was undertaken to assess the JE vaccination status of children between 12 and 36 months in the Mayurbhanj district and to determine the association between sociodemographic characteristics of study participants with JE vaccination status. Methods: To estimate the JE vaccination coverage, a cluster sampling method was adopted to conduct survey in the Mayurbhanj district of Odisha by selecting 45 clusters. Twenty children aged 12–36 months were selected from each cluster, and their mothers were interviewed about JE vaccination. House-to-house survey was conducted in selected villages. Mothers were interviewed about the knowledge on JE vaccination. Results: A total of 900 children were surveyed, of which a majority were born in government hospitals. The association between the literacy status of mothers and awareness regarding JE is found to be statistically significant. Furthermore, it was found that the association between vaccination coverage and area of residence of the beneficiaries in relation to session sites is statistically significant. Conclusion and Recommendation: The association of maternal literacy status with JE vaccination coverage was not significant, whereas the association with the awareness regarding JE was statistically significant. Four key messages of immunization should be delivered to every mother during vaccination.